Level of adaptative stress of the organism and cellular reactivity of patients with acute festering-inflammatory diseases of the kidneys and paranephral tissues - V. Stepan; R. Sydorchuk; A. Iftodiy; N. Stepan; L. Sydorchuk (Journal of Education, Health and Sport)
The frequency of purulent-septic complications in diseases of the genitourinary system remains quite high, without a noticeable tendency to decrease, which negatively affects the results of their treatment. The number of complications and relapses remains high, especially in patients of working age. The aim of the study is to research the levels of adaptive stress and cellular reactivity of the body in patients with acute purulent-inflammatory diseases of the kidneys and paranephral tissue.